2022
DOI: 10.32831/jik.v10i2.390
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Stres Kerja, Lingkungan Kerja, Motivasi, Loyalitas Dan Kepemimpinan Terhadap Kinerja Perawat Di Era Covid19

Abstract: ABSTRAK     Kinerja  seorang  perawat  dapat dilihat   dari   mutu   asuhan   keperawatan   yang diberikan  kepada  pasien,  karena  pada  dasarnya yang dijadikan acuan dalam menilai kualitas pelayanan  keperawatan  adalah  dengan menggunakan standar praktik keperawatan. Tujuan penelitian untuk mengatahui pengaruh stres kerja, lingkungan kerja, motivasi, loyalitas dan kepemimpinan terhadap kinerja perawat di era covid19 perawat di  Rumah Sakit dr. Minthohardjo Jakarta Tahun 2020. Jenis peneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Based on the gender category, the results of this study show that 79.2% of nurses are female. This result is in line with the research of Raya & Hendrawan (2022) with the results of 63.1% female respondents. A study revealed that nurses are synonymous with work done by women because it requires maternal instincts that can care with compassion and patience (Thahir & Laela, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the gender category, the results of this study show that 79.2% of nurses are female. This result is in line with the research of Raya & Hendrawan (2022) with the results of 63.1% female respondents. A study revealed that nurses are synonymous with work done by women because it requires maternal instincts that can care with compassion and patience (Thahir & Laela, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…In line with Ariasti & Handayani's (2019) research on nurse work motivation at Gembolong Hospital, where nurses with D3 Nursing Education were the most respondents in their research (84.38%). Another study on nurses' work motivation during the COVID-19 pandemic at Mintoharjo Hospital also found that nurses with D3 education were 69 (67%) (Raya & Hendrawan, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…The study shows that the majority of inpatient nurses at Malahayati Islamic Hospital Medan perform well, with 49 nurses (63.6%) categorized as having good performance, while 28 nurses (36.4%) were categorized as having poor performance. This aligns with a study by Yuniraya et al (2022), which found that 61.2% of nurses at Rumah Sakit dr. Minthohardjo Jakarta in 2021 performed well, and 38.8% performed poorly. Another study by Santari et al (2022) on nurses at Rumah Sakit Pertamina Bintang Amin Bandar Lampung found that 54 nurses (65.9%) had poor performance.…”
Section: Performance Of Inpatient Nurses At Malahayati Islamic Hospit...supporting
confidence: 91%